Business management governance: Its effect on improving the performance of small and medium industries (SMIs) during the COVID-19 pandemic - Dahmiri Dahmiri; Indra Jaya; Rista Aldilla Syafri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This research aims to analyze the effect of business management governance, which includes financial, human resources, operational and financial aspects, on improving the performance of SMIs in Jambi Province during the COVID-19 pandemic. The data collection tool is a closed questionnaire delivered online and offline. Data analysis was carried out using a qualitative approach and a quantitative approach using multiple linear regression analysis and SWOT analysis. This research concluded that financial, human resource, operational, and marketing management significantly affected the performance of SMIs in Jambi Province during COVID-19. The small and medium industries in Jambi Province during the COVID-19 pandemic were in quadrant I, meaning that the small and medium industries in Jambi Province already have strengths and opportunities to compete. Therefore SMIs in Jambi Province during the COVID-19 pandemic must carry out aggressive strategies.